The psychology of Covid-19 : building resilience for future pandemics - Vos, Joel (London : SAGE Publications Ltd, 2021)
The Psychology of Covid-19 explores how the coronavirus pandemic is giving rise to a new order in our personal lives, societies, and politics. Rooted in systematic research on Covid-19 and previous pandemics, this book describes how people perceive and respond to Covid-19, and how it has impacted a broad range of domains, including lifestyle, politics, science, mental health, media, and meaning in life. Building on this, the book then sets out how we can improve our psychological and social resilience, to safeguard ourselves against the psychological effects of future pandemics.
Includes bibliographical references and index.
Description based on XML content.
Keywords: COVID-19 Pandemic, 2020- -- Psychological aspects; COVID-19 (Disease) -- Psychological aspects; Epidemics -- Psychological aspects